BANI UMAYYAH (661-750M): PERISTIWA AMMUL JAMAAH (TAHUN PERDAMAIAN) SEBAGAI AWAL BERDIRI DINASTI BANI UMAYYAH - Syah, Muhammad Kautsar Thariq; Hambaliana, Dandie; Sa’adah, Putri Lailatus (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
The Umayyad Kingdom was founded in 41H/661 AD by Muawiyah bin Abu Sufyan and existed until 132H/750 AD. The original formation of the Umayyads occurred due to a dispute with Muawiyah (a governor from Syria). was in Damascus) when Ali bin Abu Talib became Caliph IV. previous caliphs in a different way. Abu Bakr ash-Siddiq was appointed caliph by general election. Umar bin Khaththab became caliph by being appointed directly by Abu Bakar asy-Siddiq before his death. Uthman bin Affan was appointed caliph by the Shura Council formed by Umar bin Khaththab. Meanwhile, Ali bin Abi Talib was proclaimed caliph by a section of the Muslim community with direct loyalty. After Ali's death, Hasan bin Ali's son took power. Several Muslims who supported Ali tried to stabilize the situation and conditions of Hasan's engagement as caliph. However, Mu'awiyah and his followers were not satisfied with the appointment of Hasan bin Ali and so they formed a force to wrest power from Hasan bin Ali. Mu'awiyah and his allies formed a force to stem the flow of Hasan bin Ali's followers, particularly the people of Kufa and Basra, who became his support base. In order to overcome the unrest and the political crisis, Hasan bin Ali apparently had no choice but to negotiate with Mu'awiyah to end the feud. The event of the transfer of power from Hasan bin Ali to Mu'awiyah, which took place in the city of Maskin, is called Ammul-Jama'ah (Year of Peace).